A critical survey of martial arts and academia (revised) - Williams, J. A. (2022)
In this essay, I present a survey of academic literature on the martial arts. I begin with early work on the martial arts in general including, for example, the popular Korean practice taekwondo, as well as kendo ('sword way', or Japanese fencing), and karate. My focus is on aikido and I present that analysis in the latter half. Material is presented from the disciplines of sociology, history, anthropology and very briefly psychology. For reflexive and contextual purposes I should note that I have 38 years of experience in Asian martial arts including a Korean art called tang soo do, Japanese karate, kendo and kyudo (Japanese achery). For the last 28 years I have trained with the same teacher in aikido and karate.